Smallpox in Tabasco: its impact and preventive measures (1890-1915) (Tzintzun, Revista de Estudios Históricos, 2016)
he goal of this paper is to present the measures taken in a local context (onthe example of Tabasco) to face the impact of the smallpox epidemics at theend of the 19th and the beginning of the 20th centuries in the framework ofnew control strategies such as public and medical policies which served toreduce mortality rates. his article will shed light on how eicient measureswere taken in areas far from the Mexican capital, under diicult conditionssuch as demographic dispersion, little state control, lack of standard medicalprotocols, extreme heat, lack of roads and an emphasis on inland watertransport.
Keywords: smallpox; epidemic; vaccination; local context; hygiene; Tabasco